Complete plastome sequence of Cymbidium tortisepalum var. longibracteatum (Y.S.Wu & S.C.Chen) S.C.Chen & Z.J.Liu (Orchidaceae): an endangered (EN) plant species in Southwest China. Issue 3 (2nd July 2020) - Chen, Da-Juan; Wang, Hong-Xin; Zhu, Zhi-Xin; Wang, Hua-Feng
Abstract: Cymbidium tortisepalum (Orchidaceae) has been ranked as an endangered (EN) herb species in China. In this study, we report and characterize the complete plastid genome sequence of C. tortisepalum var. longibracteatum in order to provide genomic resources helpful for promoting its conservation and garden utilization. The complete plastome is 150, 198 bp in length and contains the typical quadripartite structure of angiosperm, including two Inverted Repeat (IRs) regions of 25, 682 bp, a Large Single-Copy (LSC) region of 85, 035 bp and a Small Single-Copy (SSC) region of 13, 799 bp. The plastome contains 111 genes, consisting of 77 unique protein-coding genes, 30 unique tRNA gene and 4 unique rRNA genes. The overall A/T content in the plastome of C. tortisepalum var. longibracteatum is 62.90%. The complete plastome sequence of C. tortisepalum var. longibracteatum will provide a useful resource for the conservation and garden utilization of this species as well as for the phylogenetic studies of Orchidaceae.